Economic Analysis of First‐Line Treatment with Erlotinib in anEGFR‐Mutated Population with Advanced NSCLC. Issue 6 (June 2016) - Vergnenegre, Alain; Massuti, Bartomeu; de Marinis, Filippo; Carcereny, Enric; Felip, Enriqueta; Do, Pascal; Sanchez, Jose Miguel; Paz‐Arez, Luis; Chouaid, Christos; Rosell, Rafael
ABSTRACT : Introduction: : The cost‐effectiveness of first‐line tyrosine kinase inhibitor therapy in epidermal growth factor receptor gene ( EGFR )‐mutated advanced‐stage non–small cell lung cancer (NSCLC) is poorly documented. We therefore conducted a cost‐effectiveness analysis of first‐line treatment with erlotinib versus standard chemotherapy in European patients with advanced‐stage EGFR ‐mutated NSCLC who were enrolled in the European Erlotinib versus Chemotherapy trial. Methods: : The European Erlotinib versus Chemotherapy study was a multicenter, open‐label, randomized phase III trial performed mainly in Spain, France, and Italy. We based our economic analysis on clinical data and data on resource consumption (drugs, drug administration, adverse events, and second‐line treatments) collected during this trial. Utility values were derived from the literature. Incremental cost‐effectiveness ratios were calculated for the first‐line treatment phase and for the overall strategy from the perspective of the three participating countries. Sensitivity analyses were performed by selecting the main cost drivers. Results: : Compared with standard first‐line chemotherapy, the first‐line treatment with erlotinib was cost saving (€7807, €17, 311, and €19, 364 for Spain, Italy and France, respectively) and yielded a gain of 0.117 quality‐adjusted life‐years. A probabilistic sensitivity analysis indicated that, given a willingness to pay at least €90, 000 for 1 quality‐adjusted life‐year, the probability that a strategy of first‐line erlotinib would be cost‐effective was 100% in France, 100% in Italy, and 99.8% in Spain. Conclusion: : This economic analysis shows that first‐line treatment with erlotinib, versus standard chemotherapy, is a dominant strategy for EGFR ‐mutated advanced‐stage NSCLC in three European countries.